Macroscopic Mushroom Diversity in the Rainforest Lodges Area of Kedah Gayo Lues - Yusra Iriyanti Handayani; Iswadi iswadi; Hasanuddin Hasanuddin; Andi Ulfa Tenri Pada; Safrida Safrida (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Keywords: Diversity, mushrooms, tourist area of rainforest lodges Kedah.This study aims to determine the types of macroscopic fungi and determine the diversity of macroscopic fungi in Rainfores Lodges Kedah Gayo Lues has been conducted in September to October 2019. This study uses quantitative and qualitative approaches, with the type of research is descriptive. Sampling was done by purposive sampling technique and exploratory method (explorative), namely by direct observation to the study sites that have been determined as many as 5 stations and each station consists of 3 transects. From the results of data analysis found 30 species of macroscopic fungi that are classified into 23 families. The most dominant fungal species found are species originating from the order of Polyporales as many as 7 species and 11 species of Agaricales. The diversity of macroscopic fungi in the Kedah Rainforest Lodges area of 3.084 is included in the high category.Kata kunci : Keragaman, jamur, kawasan wisata rainforest lodges kedah. Penelitian ini bertujuan mengetahui jenis-jenis jamur makroskopis dan mengetahui keanekaragaman jamur makroskopis di Rainfores Lodges Kedah Gayo Lues telah dilakukan pada bulan September sampai dengan Oktober 2019. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif, dengan Jenis penelitian ialah deskriptif. Pengambilan sampel dilakukan dengan teknik purposive sampling dan metode jelajah (Eksploratif) yaitu dengan pengamatan langsung ke lokasi penelitian yang telah ditentukan sebanyak 5 stasiun dan masing-masing stasiun terdiri dari 3 transek. Dari hasil analisis data ditemukan 30 spesies jamur makroskopis yang diklasifikasikan ke dalam 23 familia. Spesies jamur yang paling dominan ditemukan adalah spesies yang berasal dari ordo Polyporales sebanyak 7 spesies dan Agaricales 11 spesies. Keanekaragaman jamur makroskopis pada kawasan Rainforest Lodges Kedah yaitu 3,084 termasuk kedalam kategori tinggi.